OPrlMALISASI EKSPOR KAYU LAPIS INDONESIA: (Studi Kasus Pabrik Kayu Lapis di Propinsi Sumatra Selatan) - Satria Astana; Hariyatno Dwiprabowo; Kirsfianti Linda (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
•Of the forat pfoductt in •rndonei ,. plywood haa an •im rlant '1olitio1'•in mee •the need for•t f reiln, • By the end of 1986. the contribution of plywood to the tQ.tal export value of forat pro ucta the brggest.It accounted for 61. 40 In the (Qllowingyea.r., the a.,erage gr:owthper. ye r.of the•pbwood expor.t volume was 54.98_%. . . : The a.im •of thia atudy to •know how far the a tual value• of. the plywood export aB the fore'!n exchange •Im reached the optimum. To achieve the aim, two modelB (Model• I and Model II) of linier 11rograming were conatrueted. In • thia caae, the study waa conducted on the plywood mill• in South Sumatra Province. • •The rault of the study revealB that the actual ualue of the plywood export of thia region has not been optimum. The actual value of the export per month waa USI 3 342 778 or USI 286. 1/m3. Meanwhile the export ue per month based on the optimizing model of Model I and Model II iB UBI 4 297 269 or US'824. 9/m3 and UBI 4 537 673 or UBI 343. 2/m3 respectively. To reach the optimum value of export the market area and the export volume• need to be reallocated;tJn increasein volume export by 1.35% (Model I) or by 1.04'*' (Model II) can cause a significant incre•e in the export value comj'JtJl